Adaptability Measures of Newly Established Businesses: A Case in the Philippines during the Covid 19 Pandemic (International Journal of Scientific Research and Management (IJSRM), 2022)
Establishing a business in the midst of the pandemic is very challenging since there are more factors and regulations to be considered leading to inevitable changes in the business operation to adapt with the current situation. This study aims to analyze the adaptability measures implemented by newly established food and beverage businesses. This study utilizes a quantitative approach specifically, a correlational research design to investigate the relationships between the variables with the use of a researchers’ made survey questionnaire. The instrument was distributed to twenty-three (23) respondents chosen through a convenience sampling technique based on their availability and their willingness to take part in the study. Chi-square of independence, T-test, frequency and percentage were used for data analysis. From the result, the business profile of the respondents does not affect its capability and choice of what adaptability measures it implements. In addition, the respondents were able to implement effectively the measures that they planned beforehand, as there was no significant difference with the adaptability measures during the planning and operations stage. Financial adaptability measures had the highest aggregate mean, which means it is highly implemented and highly extensive to profitability as well. This study concludes that adaptability measures regarding finance both during the planning and operations stage are significant as it affects how a business generate sales, cost, expense, and ultimately profit. Most of the other adaptability measures do not affect the profitability of the business although it is still important to be adaptable in terms of marketing and human resource.